Systematic extraction of a control-oriented model from perturbative experiments and SOLPS-ITER for emission front control in TCV. (1st June 2022) - Koenders, J.T.W.; Wensing, M.; Ravensbergen, T.; Février, O.; Perek, A.; van Berkel, M.; the TCV Team; the EUROfusion MST1 Team
Abstract: Systematic extraction of locally valid dynamic models from experiments is necessary for controller design and the validation of high fidelity models. This paper describes the extraction of a dynamic model in the form of a transfer function, giving the dynamic response of the CIII (465.0 nm) emission front position to deuterium gas puffing in the TCV divertor during flattop, relevant for heat exhaust control. The model is extracted using frequency response data from both SOLPS-ITER simulations and perturbative experiments. We use the steady-state solutions of the model SOLPS-ITER to obtain an additional data point at the zero frequency, as the identifiable frequency range by perturbative experiments is lower bounded by discharge time. We specifically approach the problem from a control engineering point of view, aiming to develop control-oriented models for the systematic design of impurity emission front controllers. We find a transfer function structure based on a diffusive process to best describe the obtained frequency response data. The resulting transfer function model accurately reproduces the local dynamic response measured during experiments, so it can be used to assess new controllers offline for similar discharge scenarios.